Advances in Twin-Screw Granulation - Valérie Vanhoorne; Ashish Kumar (Pharmaceutics, 2021)
Twin-screw granulation (TSG) is an emerging process technology that allows both wet and dry granulation of powders with a wide range of properties [...]